A new species in town: New record of Hexanchus nakamurai Teng, 1962 from the Levantine Sea. (1st November 2020) - Bengil, Elizabeth G. T.; Akbora, Hasan D.; Hadjioannou, Louis; Papageorgiou, Marios; Snape, Robin
Abstract: Hexanchus nakamurai is a deep‐water species, with very little scientific information. This study confirms the distribution of the species in the most eastern region of the Mediterranean Sea, Levantine Sea, in addition to providing some biological information from four pregnant individuals, which is being reported for the first time in the Mediterranean Sea. A total of four individuals were bycaught, in two sets on opposite coasts, three on the 13th of May 2020 from the western coast, and an individual on the 14th June 2020 from east coast of the island of Cyprus. The four specimens, all pregnant females, measured between 107 and 116 cm in total length and between 4, 330 and 4, 960 g in weight. All specimens were in early pregnancy according to the level of embryo development, which confirms that the size at maturity is smaller than previously reported. In the stomachs, remains of the hake Merluccius merluccius, the cephalopod Loligo vulgaris and two unidentified species of Hirudinea (Annelida) were found. This study provides important new information on the Mediterranean distribution of a globally rare and data deficient species, including an expansion of its known range, dietary preferences and insights of its reproduction biology; the first pregnant females reported in the Mediterranean Sea.